Graphene opens the age of two-dimensional materials - Даулетбекова A. К.; Шварц , К.; Сорокин , М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Графен открывает эпоху двумерных материалов